Role of Ultrasound in Body Stalk Anomaly and Amniotic Band Syndrome - Madhavilatha Routhu; Sreedevi Thakkallapelli; Prashanthi Mohan; Nadeem Ahmed (Hindawi Limited, 2016)
Body stalk anomaly (BSA) and amniotic band syndrome (ABS) are rare similar fetal sporadic polymalformative syndromes of unknown etiology, though there are certain differences between them. BSA is a combination of developmental abnormalities involving neural tube, body wall, and the limbs with persistent extra embryonic coelomic cavity. ABS is characterized by the presence of thin membrane-like strands attached to fetal body parts and causing constrictions and amputations. This is a cohort study involving 32,100 patients who were referred for routine antenatal ultrasound scan. The data was entered prospectively into a computer database. The duration of study was 3 years. In our study, ultrasound examination in 86 patients demonstrated ventral wall defects, craniofacial defects, and spinal and limb deformities as isolated or combined abnormalities. In those, 10 patients were suspected/diagnosed as BSA/ABS including a twin of a dichorionic diamniotic gestation. The typical features of body stalk anomaly can be detected by ultrasound by the end of the first trimester, which is important for the patient counselling and management. We are presenting these rare conditions and highlighting the importance of early sonographic imaging in diagnosing and differentiating them from other anterior abdominal wall defects.